DRAINAGE CHANNELS DESIGN AND RESTORATION OF INTER-TIDAL MARSHES - Mark E. Grismer (International Association of Lowland Technology, 2000)
Geomorphologically, inter-tidal salt marshes are vegetated landforms at elevations slightly greater than mean tidal levels that have distributed channels formed under ebb (drainage) tidal flows that widen and deepen in the seaward direction. The drainage channels enable tidal flows to circulate sediments and nutrients through the marsh system during normal tidal events, while depositing sediments during storm or seismic events. This dynamic system encourages considerable biodiversity while simultaneously providing water quality enhancement features that service marsh terrestrial life and estuary marine life. Reservoir creation, limiting sediment supply, sea level rise as well as agricultural and urban development have resultedd in significant loss of inter-tidal marshes and subsequent and adverse impacts on waterfowl, infauna and fisheries. The complex and continuously changing marsh channel hydraulic and sedimentary processes have severely constrained quantitative modeling of marsh systems such that restoration/creation efforts remain an empirical science. The purpose of this paper is to outline current understanding of salt marsh hydrodinamics, sediment accretion processes and subsequent response of marsh vegetation to set the stage for discussion of a marsh restoration/creation effort in San Paolo Bay near San Fransisco, California. Several kilometers of drainage channels were constructed in a 410 ha disturbed salt marsh to restore tidal circulation and vegetation so as to enhance habitat for threatened species (e.g. clapper rail, salt marsh harvest mouse, delta smelt and anadromous fish species). Two distinct drainage channel system (